Dairy Biomass-Wyoming Coal Blends Fixed Gasification Using Air-Steam for Partial Oxidation - Gerardo Gordillo; Kalyan Annamalai (Journal of Combustion)
Concentrated animal feeding operations such as dairies produce a large amount of manure, termed as dairy biomass (DB), which could serve as renewable feedstock for thermal gasification. DB is a low-quality fuel compared to fossil fuels, and hence the product gases have lower heat content; however, the quality of gases can be improved by blending with coals. This paper deals with air-steam fixed-bed counterflow gasification of dairy biomass-Wyoming coal blend (DBWC). The effects of equivalence ratio (1.6<Φ<6.4) and steam-to-fuel ratio (0.4<S:F<0.8) on peak temperatures, gas composition, gross heating value of the products, and energy recovery are presented. According to experimental results, increasing Φ and (S:F) ratios decreases the peak temperature and increases the H2 and CO2 production, while CO production decreases. On the other hand, the concentrations of CH4 and C2H6 were lower compared to those of other gases and almost not affected by Φ.